(untitled) (International Journal of Geoscience, Engineering and Technology, 2022)
The objective of this work was to apply the Analytical Hierarchical Process (AHP) method and geoprocessing techniques to map areas susceptible to flooding and flooding in a watershed in the municipality of Itambacuri, in Minas Gerais. The methodology was based on bibliographies that used the AHP method and included the collection, analysis and processing of spatial data for the delimitation of the study area, preparation of slope maps, altimetry, land use and occupation and flow accumulation, using the AHP techniques, which are based on mathematical methods of multi-criteria analysis to determine the factors that influence the preparation of the final mapping. It was necessary to carry out a field survey of regions with a history of floods or floods already known to validate the use of the methodology. As a result, 15 flood points and eight flood points were surveyed in the municipality, which showed satisfactory results in mapping susceptible areas of flooding, since the regions highlighted in the software coincided with the points surveyed in the field.